Underworld [videorecording (DVD)] - Beckinsale, Kate; Speedman, Scott; Sheen, Michael; Brolly, Shane; Nighy, Bill, 1949-; Leder, Erwin; Myles, Sophia, 1980-; Gee, Robbie, 1970-; Miller, Wentworth, 1972- (Columbia TriStar Home Entertainment, 2004)
A war has been raging between the Vampires and the Lycans for centuries. Selene is a vampire Death Dealer who finds out that the Lycans have plans to capture Michael. As Selene begins to track Michael, she becomes more convinced that the Lycans are planning an attack against the Death Dealers. The vampire kingpin, Kraven, is certain the Lycans do not have that kind of intelligence. As Selene shadows Michael, she finds herself wanting to protect him, but when he's attacked by Lucian, the leader of the werewolf community, and the man she wants to save has now become a sworn enemy.